1996
DOI: 10.1093/fampra/13.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer and polyps in patients aged 40 years and over who consult a GP with rectal bleeding

Abstract: A joint analysis of the two study populations showed that only age and change in bowel habit contributed to differentiating the cancer from the non-cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 7 publications
0
55
0
2
Order By: Relevance
“…Some studies included only patients with a first rectal bleed. 12,[17][18][19] All data on rectal bleeding were grouped together. Sufficient data to calculate PPVs for rectal bleeding were available in 13 papers with 18 634 participants.…”
Section: Rectal Bleedingmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies included only patients with a first rectal bleed. 12,[17][18][19] All data on rectal bleeding were grouped together. Sufficient data to calculate PPVs for rectal bleeding were available in 13 papers with 18 634 participants.…”
Section: Rectal Bleedingmentioning
confidence: 99%
“…Sufficient data to calculate PPVs for rectal bleeding were available in 13 papers with 18 634 participants. 11,12,14,[17][18][19][20][21][22][23][24][25][26] This is displayed as a Forest plot ( Figure 1A). The PPV ranged from 2.2% 18 to 15.8%.…”
Section: Rectal Bleedingmentioning
confidence: 99%
See 2 more Smart Citations
“…One in five patients reporting rectal bleeding was not investigated Á/ one possible explanation could be that a diagnosis was established by clinical examination (haemorrhoids) or that the recorded rectal bleeding (and a diagnosis) had been present earlier. In a Danish prospective study on rectal bleeding, Norrelund (16) found new onset of rectal bleeding or changes in bleeding pattern related to colorectal cancer, whereas this could not be shown in patients with a known tendency for rectal bleeding and with no change in the bleeding pattern. Unintended weight loss was left uninvestigated in 27% of the patients.…”
Section: Discussionmentioning
confidence: 91%